2011
DOI: 10.18632/oncotarget.256
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mycoplasma hominis infection with prostate cancer

Abstract: The origin of chronic inflammation preceding the development of prostate cancer (PCa) remains unknown. We investigated possible involvement of mycoplasma infection in PCa by screening prostate biopsies from two groups of Russian men undergoing PCa diagnosis. M. hominis was detected by standard PCR in 15% of the 125 patients in the first group and by quantitative real-time PCR in 37.4% of the 123 men in the second group. In both groups, stratification of patients according to diagnosis showed that M. hominis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 18 publications
(21 reference statements)
2
97
0
2
Order By: Relevance
“…By using qPCR and freshly isolated DNA samples, M. hominis infection was shown to be associated with prostate cancer (32). However, extracting mycoplasma DNA from formalin-fixed tissues is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…By using qPCR and freshly isolated DNA samples, M. hominis infection was shown to be associated with prostate cancer (32). However, extracting mycoplasma DNA from formalin-fixed tissues is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by our in vitro findings, we recently undertook a clinical study in which we looked at the presence of mycoplasma in the prostates of men suspected of having prostate cancer due to elevated prostate-specific antigen (PSA) levels. 66 Mycoplasma hominis was detected in more than 30% of prostate biopsies. Stratification of patients according to diagnosis showed that M. hominis was present at 3 times higher frequency in patients with prostate cancer than in those with benign prostatic hyperplasia.…”
Section: Nf-κb Against P53: a Double-edged Swordmentioning
confidence: 99%
“…for the natural substrates of PNP Hyor , for 2-chloro-29-deoxyadenosine (cladribine) and 2-fluoroadenine-arabino-furanoside (fludarabine), and for P i were determined using nonlinear regression analysis (using GraphPad Prism 5) from data obtained in at least two independent experiments. at ASPET Journals on May 11, 2018 molpharm.aspetjournals.org Huang et al, 2001;Pehlivan et al, 2004Pehlivan et al, , 2005Yang et al, 2010;Apostolou et al, 2011;Barykova et al, 2011;Urbanek et al, 2011;Erturhan et al, 2013) and other prokaryotes (reviewed by Mager, 2006;Cummins and Tangney, 2013) have been found to associate preferentially with tumor cell tissue in cancer patients, our findings may be of relevance for cancer chemotherapy and may argue for a personalized treatment schedule based on the microbiotic tumor environment. A drug administration protocol combining certain anticancer purine derivative drugs with a PNP inhibitor could therefore increase therapeutic efficiency.…”
Section: Discussionmentioning
confidence: 52%
“…Additionally, little information is available on the extent of a mycoplasma infection in tumors (i.e., actual numbers present at the tumor site). A single study has determined the amount of M. hominis 16s rRNA present in prostate cancer tissues by quantitative real-time polymerase chain reaction and reported to be ∼9.1 Â 10 5 copies/g tissue (Barykova et al, 2011), but it is unclear whether this also applies to an infection of different mycoplasmas (e.g., M. hyorhinis) in other tumors. Nevertheless, a rational choice for drugs that display an increased cytostatic activity after metabolism by mycoplasma-encoded enzymes present in the local environment of a tumor could result in a more pronounced therapeutic selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation